Effect of Various By-products on the Egg Quality of Laying Hens (Gallus domesticus) - Naseer, Adeeba; Raziq, Sumaira; Muneer, Muhammad; Usman, Muhammad; Ahmad, Maqsood; Muhammad Asad Ullah; Khadim, Ayesha; Mushtaq, Hafsa; Mubashar Ali, Hafiz Muhammad; Şahin, Tarkan (Indus Journal of Bioscience Research, 2025)
This study was aimed to investigate the effects of byproducts on egg quality of white layer hens. A total of 18 hens 28-week old were brought to Animal Toxicology Laboratory of Zoology Department, The Islamia University of Bahawalpur, Pakistan. After habituation, hens were acclimatized with the research laboratory conditions for seven days. A total 18 birds of white laying hens were randomly divided to three groups each group contained six hens. The hens were kept at a photoperiod of 16 h/8 h light/dark cycle, and a room temperature of 25 °C ± 2°C. Feed and water were provided ad libitum and the experiment lasted for five weeks. Birds were offered either a basal diet or the basal diet supplemented with 150, 170 or 190 g/kg of egg shells and tea byproducts. As a result of this study, there were significant differences in egg production and egg weight. The number of egg and egg weight were significantly reduced in byproducts group. There were no significant differences in egg length and egg white weight. However egg width and egg shell thickness were significantly decreased in byproducts group. In summary, egg shell and tea byproducts can be used as an alternative feedstuff in laying hen diets at inclusion levels up to 190 g/kg without any negative impact on performance and egg quality traits. Further studies are needed to determine the level of inclusion of byproducts that does not affect performance.